2020
DOI: 10.1111/hepr.13572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol consumption on multiple hepatocarcinogenesis in patients with fatty liver disease

Abstract: The number of patients with fatty liver disease (FLD) is increasing globally. Ethanol consumption in FLD is known to be associated with an increased risk of hepatocellular carcinoma (HCC), but the effects of alcohol consumption on the occurrence of multiple HCCs remain unclear. We explored the relationship between the daily ethanol intake and the HCC number. Methods: This single center retrospective study enrolled 114 patients without viral or immune hepatitis undergoing first line HCC treatment who had been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Even mild-to-moderate alcohol intake has been reported to worsen hepatic fibrosis and increase mortality. 4,[29][30][31][32][33] Recently, phosphatidylethanol, a biological marker for alcohol consumption, has been reported to be useful in predicting advanced fibrosis in patients with non-alcoholic fatty liver disease (NAFLD) who have moderate alcohol consumption. 34 Thus, it is also important to assess fatty liver independent of alcohol intake.…”
Section: Rationalementioning
confidence: 99%
“…Even mild-to-moderate alcohol intake has been reported to worsen hepatic fibrosis and increase mortality. 4,[29][30][31][32][33] Recently, phosphatidylethanol, a biological marker for alcohol consumption, has been reported to be useful in predicting advanced fibrosis in patients with non-alcoholic fatty liver disease (NAFLD) who have moderate alcohol consumption. 34 Thus, it is also important to assess fatty liver independent of alcohol intake.…”
Section: Rationalementioning
confidence: 99%
“…Usually, chronic liver diseases along with cirrhosis caused by infections from hepatitis B and C are associated with hepatocellular carcinomas (HCC) that drive Liver cancers [42]. Long-term liver diseases include the major risk factors for HCC, which is considered the primary liver cancer [44] along with the accumulation of fat in the liver and higher alcohol consumption [45]. The liver function blood tests, imaging tests, and liver biopsies are the standard procedures for the diagnosis of liver cancer [46].…”
Section: Liver Cancermentioning
confidence: 99%
“…Alcohol use at least four times per week annually along with obesity (BMI > 30) increases the incidence of HCC [61]. Kimura et al found that mild alcohol use (<20 g/day) in patients with NASH and advanced fibrosis was associated with a significant increase in the risk of HCC [62], while Ochiai et al showed that ethanol intake ≥ 40 g was associated with a significant increase in multinodular HCCs [63].…”
Section: Lifestyle Risk Factorsmentioning
confidence: 99%